Autoregulation of Pulsatile Bioprosthetic Total Artificial Heart is Involved in Endothelial Homeostasis Preservation - Smadja, David M.; Chocron, Richard; Rossi, Elisa; Poitier, Bastien; Pya, Yuri; Bekbossynova, Mahabbat; Peronino, Christophe; Rancic, Jeanne; Roussel, Jean Christian; Kindo, Michel; Gendron, Nicolas; Migliozzi, Ludovica; Capel, Antoine; Perles, Jean Christophe; Gaussem, Pascale; Ivak, Peter; Jansen, Piet; Girard, Claude; Carpentier, Alain; Latremouille, Christian; Guerin, Coralie; Netuka, Ivan (Thrombosis and Haemostasis, 2020)
Pulsatile Carmat bioprosthetic total artificial heart (C-TAH) is designed to be implanted in patients with biventricular end-stage heart failure. Since flow variation might contribute to endothelial dysfunction, we explored circulating endothelial biomarkers after C-TAH implantation in seven patients and compared the manual and autoregulated mode. Markers of endothelial dysfunction and regeneration were compared before and during a 6- to 9-month follow-up after implantation. The follow-up was divided into three periods (< 3, 3–6, and > 6 months) and used to estimate the temporal trends during the study period. A linear mixed model was used to analyze repeated measures and association between tested parameters according to the mode of C-TAH and the time. Relevance of soluble endoglin (sEndoglin) level increase has been tested on differentiation and migration potential of human vasculogenic progenitor cells (endothelial colony forming cells [ECFCs]). Normal sEndoglin and soluble endothelial protein C receptor (sEPCR) levels were found in patients after implantation with autoregulated C-TAH, whereas they significantly increased in the manual mode, as compared with pretransplant values (p = 0.005 and 0.001, respectively). In the autoregulated mode, a significant increase in the mobilization of cytokine stromal cell-derived factor 1 was found (p = 0.03). After adjustment on the mode of C-TAH, creatinine or C-reactive protein level, sEndoglin, and sEPCR, were found significantly associated with plasma total protein levels. Moreover, a significant decrease in pseudotubes formation and migration ability was observed in vitro in ECFCs receiving sEndoglin activation. Our combined analysis of endothelial biomarkers confirms the favorable impact of blood flow variation achieved with autoregulation in patients implanted with the bioprosthetic total artificial heart.
Keywords: bioprosthetic total artificial heart; biomarker; endothelial; sEPCR; sEndoglin; endothelial progenitors; ECFC